Development of UV-curable liquid for in-liquid fluorescence alignment in ultraviolet nanoimprint lithography. (14th May 2018) - Ochiai, Kento; Kikuchi, Eri; Ishito, Yota; Kumagai, Mari; Nakamura, Takahiro; Nakagawa, Masaru
Abstract: We studied a fluorescent UV-curable resin suitable for fluorescence alignment in UV nanoimprinting. The addition of a cationic fluorescent dye caused radical photopolymerization of a UV-curable resin by exposure to visible excitation light for fluorescence microscope observation. The microscope observation of a resin film prepared by pressing resin droplets on a silica substrate with a fluorinated silica superstrate revealed that the cationic dye molecules were preferably adsorbed onto the silica surface. It was indicated that the dye molecules concentrated on the silica surface may cause the photocuring. A nonionic fluorescent dye was selected owing to its low polar symmetrical structure and its solubility parameter close to monomers. The fluorescent UV-curable resin with the nonionic dye showed uncured stability to exposure to visible excitation light for 30 min with a light intensity of 8.5 mW cm −2 detected at 530 nm.